Calculation of Student Savings with Monthly Contributions and Gradual Use Using Definite Integrals - Gurning, Yeremia Setya Maharman; Waruwu, Pedro Stella Mario Meyar; Nasution, Aurela Khoiri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to calculate student savings balances by considering continuous monthly contributions and gradual expenditure using a definite integral approach. Using the descriptive quantitative method, data was collected through an online questionnaire survey involving five respondents. Data analysis uses a definite integral formula implemented through MATLAB software, producing a projection of each student's savings balance within a 6 month period. The research results show that the integral approach is certainly effective in modeling the growth of savings balances. Respondents who are disciplined in saving with little spending tend to have a significant positive balance, while those whose savings contribute less than their spending experience a deficit. Simulation with MATLAB makes it easier to visualize and plan students' finances. This approach provides important insights into personal financial management, particularly in saving regularly and understanding the impact of continuous interest. It is hoped that these findings can help students improve financial literacy and make financial planning more effective.